Working Capital Analysis of Public State Undertaking (A Case Study of Madhya Pradesh State Electricity Board) - Khatik, S. K.; Jain, Rashmi (Indian Journal of Finance, 2009)
The term working capital refers to current assets, which may be defined as those, which are convertible into cash or equivalents within a period of one year and those which are required to meet day to day operations. The working capital management refers to management of the working capital or to be more precise the management of current assets. A firms working capital consist of its investments in current assets which indicates short term assets such as cash and bank balance, inventories, receivables and advances. So the working capital management refers to the management of the level of all these individuals current assets.Keeping this in view, we have tried to evaluate working capital of MPSEB during the period from 1995-96 to 2004-05. This research article highlights concept of working capital, working capital policy, components of working capital and factors affecting working capital of MPSEB during the last 10 years and identify which factors are responsible for the improvement of working capital of the company. Working capital position of MPSEB has been analyzed under four categories like analysis of liquidity ratio, analysis of liquidity position, component wise analysis of working capital and analysis of liquidity ranking. Finally it was found that working capital position of MPSEB is not satisfactory during the study period and also found that current assets are less than current liabilities which leads to negative and unfavorable working capital. Short term solvency or liquidity position depends upon current assets and current liabilities, if current assets are more than current liabilities, it means organization have good liquidity position. In this light MPSEB should try to increase their current assets specially in cash and bank and inventory and try to curtail their current liabilities specially creditors and outstanding expenses for improvement of short term solvency and liquidity position as well as expedite benefits of working capital.